Retrospectiva sociolingüística: contribuições do PEUL - Paiva, Maria da Conceição de; Scherre, Maria Marta Pereira (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
In this article we focus PEUL’s (Programa de Estudos sobre o Uso da Língua) contribution to Brazilian Sociolinguistics, and, specifically, to variationist studies. We start by providing an overview of Rio de Janeiro variable phenomena. Then we show the spread of variation domain and emphasize the systematicity and regularity of a linguistic variable - the formal parallelism - on phenomena of language variation and change, and show some patterns of correlation between language and social structure.